Opinion Leaders, Perceived Media Hostility and Political Participation. Issue 5 (19th October 2020) - Tsang, Stephanie Jean; Rojas, Hernando
ABSTRACT: Opinion leaders play a significant role in public opinion formation by highlighting, defining and framing political issues for their circle of friends. Although we know opinion leaders are more likely to participate in politics, we are less sure about how they process mediated information and what motivate them to participate more actively than individuals who are less politically active. Data from a national representative survey in Colombia show not only that opinion leaders perceive more media bias and hostility, but also that the degree of their perceived media hostility is capable of motivating higher levels of political talk and participation.